2009
DOI: 10.1124/mol.108.054312
|View full text |Cite
|
Sign up to set email alerts
|

Met909 Plays a Key Role in the Activation of the Progesterone Receptor and Also in the High Potency of 13-Ethyl Progestins

Abstract: Many progestins have been developed for use in contraception, menopausal hormone therapy, and treatment of gynecological diseases. They are derived from either progesterone or testosterone, and they act by binding to the progesterone receptor (PR), a hormone-inducible transcription factor belonging to the nuclear receptor superfamily. Unlike mineralocorticoid, glucocorticoid, and androgen receptors, the steroid-receptor contacts that trigger the switch of the ligand-binding domain from an inactive to an active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 34 publications
(41 reference statements)
3
34
0
1
Order By: Relevance
“…Interestingly, this structure showed that the PR homodimer structure is smaller and less stable than previously published RXR and ER dimer structures. Other structures have been solved with PR LBD bound to synthetic ligands, including metribolone, mometasone furoate, norethindrone, tanaproget, mifepristone, levonorgestrel, and several pyrrolidine ligands (Matias et al, 2000;Madauss et al, 2004;Zhang et al, 2005;Petit-Topin et al, 2009;Raaijmakers et al, 2009;Thompson et al, 2009;Kallander et al, 2010). Two other structures were published showing PR bound to asoprisnil and corepressor proteins, specifically NCoR and SMRT (Madauss et al, 2007).…”
Section: A Progesterone Receptor Structurementioning
confidence: 99%
“…Interestingly, this structure showed that the PR homodimer structure is smaller and less stable than previously published RXR and ER dimer structures. Other structures have been solved with PR LBD bound to synthetic ligands, including metribolone, mometasone furoate, norethindrone, tanaproget, mifepristone, levonorgestrel, and several pyrrolidine ligands (Matias et al, 2000;Madauss et al, 2004;Zhang et al, 2005;Petit-Topin et al, 2009;Raaijmakers et al, 2009;Thompson et al, 2009;Kallander et al, 2010). Two other structures were published showing PR bound to asoprisnil and corepressor proteins, specifically NCoR and SMRT (Madauss et al, 2007).…”
Section: A Progesterone Receptor Structurementioning
confidence: 99%
“…X-ray crystallography studies of PR bound to the 11␤-substituted steroids, asoprisnil (20) and RU486 (21), along with the full PR agonist levonorgestrel (22) clearly indicate a crucial function for Met 909 in the agonism/antagonism balance. This has also been shown to be true for nonsteroidal SPRMs (11,12).…”
mentioning
confidence: 99%
“…Fig. 6 shows the overlap at these four sites and some other residues in the steroid binding domain of the "ancestor-like" 3D model and the crystal structure of wildtype human PR complexed with progesterone [15,[32][33][34]. There is excellent overlap of all amino acids.…”
Section: Sequence Analysis Of Helix 3 Through Helix 5 In Fish Prsmentioning
confidence: 91%
“…A 59 residue segment from the human PR corresponding to helix 3 through helix 5 [15,16,27,[32][33][34] was used as a probe by BLAST to search GenBank and Ensembl for the corresponding segment in [29,46], but not in humans [49,50]. 15␣-Hydroxy-progesterone may be the active progestin in lampreys [15,47,48].…”
Section: Analysis Of Pr Sequencesmentioning
confidence: 99%